Characterization of Ibuprofen Solid Dispersion Part-II: FT-IR and DFT studies - ARSLAN, HAKAN; OZLEN SAHIN, NEFISE (Asian Journal of Chemistry, 2010)
The Fourier transform infrared spectra of ibuprofen (2-[4-(2-methylpropyl)phenyl]propanoic acid), skimmed milk powder and solid dispersion of ibuprofen was recorded in the solid phase. The equilibrium geometry, harmonic vibrational frequencies and infrared intensities of ibuprofen were calculated by density functional B3LYP method with the 6-311G(d,p) basis set. The scaled theoretical wavenumbers showed very good agreement with the experimental values. A detailed interpretations of the infrared spectra of ibuprofen is reported. Comparison of FT-IR spectra of plain drug, skimmed milk powder and solid dispersion of ibuprofen indicates that a chemical interaction takes place between skimmed milk and ibuprofen while forming the inclusion complex for solid dispersion.